2021
DOI: 10.1039/d0ee03679j
|View full text |Cite
|
Sign up to set email alerts
|

Advanced manufacturing for electrosynthesis of fuels and chemicals from CO2

Abstract: Changing the reactor design paradigm for improved CO2 electrolyzers through advanced manufacturing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
84
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 70 publications
(88 citation statements)
references
References 62 publications
4
84
0
Order By: Relevance
“…Separately, the development of high-performance CO 2 -fed electrolyzers has undergone a renaissance over the past decade leading to record selectivity, current density, and single pass conversion. 2,18–21 These gains were realized in large part through the understanding that new electrolyzer designs were needed to improve the electrolyte and CO 2 transport to the catalyst surface improving the local catalyst environment. This allowed researchers to approach the intrinsic activity of the electrocatalysts.…”
Section: The Promise Of Electrifying Bioreactorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Separately, the development of high-performance CO 2 -fed electrolyzers has undergone a renaissance over the past decade leading to record selectivity, current density, and single pass conversion. 2,18–21 These gains were realized in large part through the understanding that new electrolyzer designs were needed to improve the electrolyte and CO 2 transport to the catalyst surface improving the local catalyst environment. This allowed researchers to approach the intrinsic activity of the electrocatalysts.…”
Section: The Promise Of Electrifying Bioreactorsmentioning
confidence: 99%
“…This allowed researchers to approach the intrinsic activity of the electrocatalysts. 20 We propose that a similar paradigm shift in reactor design and materials is needed to maximize the performance of biological catalysts in electrified bioreactors.…”
Section: The Promise Of Electrifying Bioreactorsmentioning
confidence: 99%
“…For example, using advanced manufacturing methods (e.g., 3D printing), Corral et al decreased the distance between the cathode and anode, which successfully reduced the total cell resistance from 33.1 to 21.2 Ω in a neutral flow cell system and led to state-of-theart ethanol production under neutral conditions. [63] Alternatively, using CO instead of CO 2 as the feed gas can avoid the neutralization of alkaline electrolytes. The conversion of CO 2 to alcohols can be divided into two steps.…”
Section: Reactor Designmentioning
confidence: 99%
“…32 This can be true even for microfluidic GDE electrolyzer designs with a catholyte flow field where it has been shown that lower volatility products such as ethanol can change the wetting behavior of the GDE leading to electrolyte penetration causing mass transport limitations. 33 In this work, we explore the use of hierarchical nanoporous gold (hnpAu) liquid phase flow-through electrodes to control and eliminate the effects of diffusion limitations on ECR as outlined above. A gold catalyst was used for its well-known high selectivity for CO 2 -to-CO reduction which simplifies the gas product analysis.…”
Section: Introductionmentioning
confidence: 99%